Determinação de propriedades biológicas e prospecção fitoquímica dos extratos das folhas de Physalis angulata L., silvestre e cultivada - Dias, Flayanna Gouveia Braga (2019)
The diversity of plants worldwide, as well as chemical variation implies a large amount of bioactive substances. The use of plant extracts with b iological properties appears as a viable, healthy and less expe nsive alternative when compared to synthetic substances. In this context, the objective of this research was to carry out a phytochemical screening and to evaluate the aqueous extracts of the l eaves of Physalis angulata L., wild and cultivated, regarding the influence of the extraction method and plant material on the bioaccessibility of bioactive compounds, antioxidant activity, activity antimicrobial, as well as their toxicity on the microcrus tacean Artemia salina. The extracts were obtained from wild and cultivated leaves of Physalis angulata and three different extractive methods (decoction, maceration and assisted by ultrasound). These were evaluated using one dimensional hydrogen 1 (1H NMR) and carbon 13 (13C NMR) nuclear magnetic resonance spectra, be fore and after solid phase extraction, quantification of bioactive compounds before and after gastrointestinal digestion in vitro, antioxidant activity by spectrophotometric methods (ABTS • a nd DPPH), antimicrobial activity by agar diffusion methods, bro th microdilution, morphological damage to bacterial cells (Transmission Electron Microscopy, in addition to toxicity using the Artemia salina microcrustacean. variance showed significant differ ences in the interaction between the extractive methods and the type of plant material studied. The extracts of wild and cultivated leaves obtained by decoction showed, respectively, the highest levels of phenolic compounds (15310.79 and 8115.95 mg EAG 10 0 g of dry extract) and, consequently, greater antioxidant poten tial for both analytical methods (ABTS • and DPPH), differing significantly from the other extractive methods. The bioaccessibility indexes of phenolic compounds in the extracts were reduced (45.2% to 87.8%) after simulated gastrointestinal digestion, pr esenting low antioxidant potential when compared to data obtained before digestion. The antimicrobial potential of the extracts was observed only against Gram positive bacteria by both analyti cal methods, presenting CMI's between 1.0 and 25 mg / mL for Sta phylococcus aureus and 2.5 to 6.25 mg / mL for Listeria monocytogenes, also being observed the morphological damage caused to bacterial cells through transmission electron microscopy images. The methanolic fractions of cultivated leaf extracts obtained by decoction and assisted by ultrasound also showed antimicrobial potential on Gram positive microorganisms with MICs of 1.0 mg / mL of both extracts on Staphylococcus aureus and of 2.7 mg / mL a nd 1.0 mg / mL on Listeria monocytogenes , respectively. The anti microbial potential of these extracts can be attributed to vitanolide 4x hydroxyvitanolide E identified in the 1H NMR and 13C NMR spectra as the major compound. The aqueous extracts of Physalis angulata with antimicrobial and antioxidant potential, as well as their respective fractions (methanolic and aqueous) did not present toxicity (LC50 > 1000 µg / mL) on the microcrustacean Artemia salina presenting potential for application in food, thus avoiding the use of organic solvents and synthetic substances.